Willingness to Communicate in Foreign Language: The Effects of Confidence and International Posture - Mbau, Anitha Thalib; Rahman, Nadya Septiani; Nurlaela, Nurlaela (English Education and Literature Journal (E-Jou), 2024)
Understanding student’s language communicative behaviors is crucial to explain why some students might have more willingness to communicate (WTC) when they are learning English than other students. WTC is one important factor contributing to student’s success in developing their speaking skills with its relation to other aspects. This study intended to examine the level of students’ willingness to communicate during a speaking class, WTC outside the classroom, communication confidence, and international posture and to see the correlation among those variables. The data were collected through a questionnaire adapted from a willingness to communicate in the L2 scale. The result shows that most Indonesian students majoring in English Education at Yogyakarta State University in the Special Region of Yogyakarta have a high willingness to communicate during a speaking class as well as international posture. Furthermore, half of the students have high and moderate willingness to communicate outside the classroom and communication confidence. However, there is only one correlation among those variables that is found significant which is a correlation between WTC during a speaking class and communication confidence. Since this study did not find any participant who had a low rank for all the variables tested, this study has limitations in explaining the path from low to high level of the four variables.